Kandungan Senyawa Fitokimia dan Aktivias Antioksidan dari Ekstrak Daun Alpukat (Persea americana Mill.) : Narrative Review - Michelle Jovelyna My Angel Pasaribu; Ihsanti Dwi Rahayu; Muhammad Iqbal; Ari Sri Ulandari (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Avocado leaves have long been used by Indonesian people as traditional medicine. Many studies have shown that the plant has many active compounds that have the potential to prevent cell damage caused by free radicals. The purpose of this narrative review article is to collect and review references related to the phytochemical compound content and potential antioxidant activity of avocado leaf extract (Persea americana Mill.). The search and review of literature used in writing this article was carried out by searching for reference sources by combining relevant keywords such as "antioxidant AND persea americana leaves* AND extract" on database sites such as NCBI, ScienceDirect, and Google Scholar. There are inclusion criteria used, namely articles in English and Indonesian, available in full text form, discussing secondary metabolite compounds of avocado leaf extract using the maceration method, and discussing antioxidant activity tests using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Based on the search results, there are 7 articles that have met the inclusion criteria and have been reviewed. The results of this narrative review obtained information that there were several studies that conducted antioxidant activity tests on avocado leaf extract using the DPPH method with an IC50 value range of 6.7-440.80 µg/ml and there were polyphenol compounds, especially quercetin and kaempferol which contributed to the antioxidant activity of avocado leaves.